Foamy oil properties and horizontal well inflow performance relationship under solution gas drive. Issue 3 (4th May 2019) - He, Congge; Fan, Zifei; Xu, Anzhu; Zhao, Lun
ABSTRACT: In this study, we modified the foamy oil fluid property model by defining the coalescence rate constant to account for the fraction of entrained gas in the oil phase. The modified model was verified by matching the calculated results with experimental data. Then, the horizontal well inflow performance of foamy heavy oil reservoirs was calculated by incorporating the modified fluid properties into the horizontal well flow rate equation at pseudo-steady state. In addition, the horizontal well inflow performance of foamy oil under solution gas drive and the corresponding conventional oil was compared. The results show that the foamy oil fluid properties calculated by the modified fluid property model are consistent with the experimental results, thus verifying the correctness of the model. Comparing the horizontal well inflow performance of foamy oil and conventional oil, it shows that when the average reservoir pressure is between bubble point pressure and pseudo-bubble point pressure, the flow rate of foamy oil is higher than that of the conventional oil. When the average reservoir pressure drops below the pseudo-bubble point pressure, the flow rate of foamy oil is close to that of the conventional oil. Foamy efficiency, defined as the ratio of the difference between the flow rate of foamy oil and conventional oil to the conventional oil flow rate, has the biggest value, about 15%, close to the pseudo-bubble point.